Comparison between clinical and ultrasonographic parameters in predicting difficult airway: An observational prospective study - Poudel, Deepak; Pyakurel, Kumud; Sah, Birendra Prasad; Pokhrel, Anuja; Khanal, Kanak; Rajbanshi, Lalit K (Birat Journal of Health Sciences, 2023)
Introduction : Various clinical tests are applied at the bedside to predict difficult airway during the pre-anaesthetic examination. Ultrasonography can be used to evaluate the airway and predict difficulty in laryngoscopy and endotracheal intubation.Objective : To compare the various clinical and ultrasonographic parameters in predicting difficult airway.Methodology: This prospective observational study was carried out at Birat Medical College and Teaching Hospital. The clinical parameters obtained were Modified Mallampati Grade (MMP), Upper Lip Bite Test (ULBT) and Thyromental Distance (TMD) and the ultrasonographic (USG) parameters used were Tongue Volume (TV), Hyomental Distance Ratio (HMDR) and distance of soft tissue from skin to hyoid bone (DSHB).These results were correlated with Cormack-Lehane (CL) grade during laryngoscopy of 200 patients. The sensitivity, specificity, Receiver Operating Characteristic (ROC) curve along with Area under the curve (AUC) was calculated for each parameter.Result: Incidence of difficult airway was 15.5%. The sensitivity and specificity of ultrasonographic tongue volume (TV) was higher among all parameters in predicting difficult airway. The specificity of HMDR and DSHB were better compared to clinical parameters.Conclusion: The use of ultrasound in pre-anaesthetic examination can be a viable tool along with clinical parameters for prediction of difficult airway.